Research on the application of 700 MHz frequency band in 5G network optimization - Yejiang ZHANG; Lei SUN; Yiyan YIN; Xiaokang YANG; Jian HU (Dianxin kexue)
The 700 MHz frequency band has the advantages of low frequency, strong diffraction ability, and good coverage effect.China Mobile and China Radio and Television had made it clear that they would jointly build and share 5G networks based on 700 MHz frequency band resources.Firstly, the coverage advantages of 700 MHz frequency band were analyzed theoretically, and then the pilot projects such as 700 MHz 5G station continuous road coverage test, residential building coverage performance test and fixed-point capacity performance test provided data support for the subsequent 700 MHz 5G network construction and optimization.It could release the value of 700 MHz gold spectrum to the greatest extent and continuously improve the quality of 5G wireless network from the aspects of actively avoiding 700 MHz radio and television frequency interference, giving full play to the advantages of high and low frequency networking schemes, and actively exploring multi band collaborative optimization strategies.